(untitled) (Journal of Medicine, 2024)
Background: Wellbeing of the elderly population in terms of their health and nutritional status are often ignored and unidentified in the community. This study aimed at assessing the nutritional status of the geriatric patients and their quality of life (QOL) attending OPD of Mugda Medical College Hospital. Method: This survey was conducted in the OPD of Mugda Medical College Hospital from June to December 2022 through a cross-sectional analytical method. The study tools were the Mini-Nutritional Assessment tool and WHOQOL-BREF questionnaires which were used to observe the level of nutrition and quality of life among geriatric population respectively. Result: Of all the respondents, about half (46%) were at risk for malnutrition and about 28% were malnourished while 26% respondents’ level of nutrition was normal. About 62% respondents had poor QOL, whereas, 31% had fair QOL and only 7% had good QOL. Also, nutritional status and quality of life of the elderly had significant relationship. Conclusion: The impact of poor nutrition on the quality of life and physical ability of geriatric population is remarkably worthy of attention. The ageing process is challenging and raises public health concerns. Reduction of the observed prevalence of malnutrition and thereby upgrading the quality of life of elderly population should be more focused on and proper attention to this issue is crucial in the community as well as national level. J MEDICINE 2024; 25: 29-34